Rapidly fluctuating anisotropy parameter in the near-threshold photodissociation of NO2 - Monti, O; Dickinson, H; Mackenzie, S; Softley, T (2000)
A novel experiment for near-threshold photodissociation studies is presented. State-selective excitation of the molecular photofragments to high-n Rydberg states is used in a variation of the ion imaging technique, allowing for undistorted detection of slow fragments produced close to the channel dissociation threshold. As a first demonstration of this method, the angular anisotropy parameter β for production of NO (J = 17/2) and O3P2 in the photodissociation of NO2 has been obtained as a function of excess energy. A classical model for β as a function of excess energy is presented, accounting for the decrease of anisotropy in the angular photofragment distribution upon approaching the channel threshold. The experimental values of β fluctuate substantially around the values predicted by the model, indicating strong underlying fluctuations in the state-to-state rate constant. This experiment offers in principle a unique route to measuring state-to-state reaction rate constants in situations where existing time- or frequency-resolved methods are inappropriate. © 2000 American Institute of Physics.